Analysing media discourses - Burridge, Joseph D. [ (Joseph David)]; Richardson, John E. (Routledge, 2011)
The continual growth in the significance of mass-mediated communication makes it essential that we are able to reflect upon and critically appreciate the semiotic processes that are involved in their impact upon social and cultural life. This edited collection showcases a range of diverse approaches to the analysis of various forms of mediated communications, including varying degrees of attention to their associated textual, discursive and social practices. Individual contributions are devoted to exploring, in analytical depth,...